1997
DOI: 10.1046/j.1365-3024.1997.d01-209.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to the filaria Litomosoides sigmodontis in susceptible and resistant mice

Abstract: Comparisons were made between the immune responses evoked during the course of chronic and patient infections of Litomosoides sigmodontis in susceptible BALB/c mice and non-patent infections in resistant B10.D2 mice. Early antigen specific responses of spleen cells were weak in both mouse strains. However, by day 58 post infection a strong Th2 response, as determined by production of IL-4, IL-5 and IL-10, was observed in BALB/c mice but not in B10.D2 mice. Antibody responses seemed to appear sooner in B10.D2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
62
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 21 publications
7
62
1
Order By: Relevance
“…Together with the findings that neither cellular composition nor production of Th1/ Th2 cytokines differed between CCL17 E/+ and CCL17 E/E mice, our data suggest that induction of effector or regulatory cells is not the major mode of action of CCL17 in early murine filarial infections. This is also in accordance with earlier observations that differences in parasite survival were obvious already at day 10, and it has been shown that the proportion of worms that establish themselves in the host following the entry of infective L3 is determined during the first days [i.e., at times before adaptive immune responses can control the immune reaction (29,31,32)]. …”
Section: Discussionsupporting
confidence: 92%
“…Together with the findings that neither cellular composition nor production of Th1/ Th2 cytokines differed between CCL17 E/+ and CCL17 E/E mice, our data suggest that induction of effector or regulatory cells is not the major mode of action of CCL17 in early murine filarial infections. This is also in accordance with earlier observations that differences in parasite survival were obvious already at day 10, and it has been shown that the proportion of worms that establish themselves in the host following the entry of infective L3 is determined during the first days [i.e., at times before adaptive immune responses can control the immune reaction (29,31,32)]. …”
Section: Discussionsupporting
confidence: 92%
“…In L. sigmodontis infection, maximal parasite Ag-driven IL-4 and IL-5 production from splenocytes was previously found to occur at 10-12 wk p.i. (34). and maximal IL-4 and IL-5 cytokine transcripts at 4 to 5 wk p.i.…”
Section: Discussionmentioning
confidence: 96%
“…They molt to fourth-stage larvae (L4) within 10 d and to young adults within 26-28 d. In the permissive BALB/c strain, L. sigmodontis mate and release MF by day 60 postinfection (p.i.) (24). Young adults never reach sexual maturity in the resistant C57BL/6 mice and are removed by granuloma formation by day 60 p.i.…”
mentioning
confidence: 99%